Conductive paste, highly thermally conductive material and semiconductor device
A conductive paste with tailored viscosity characteristics addresses the challenges of bonding, conductivity, and heat dissipation in semiconductor devices, while preventing protrusion and contamination, thereby enhancing the reliability of semiconductor devices.
Patent Information
- Application Number
- JP2021007195
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-01-20
AI Technical Summary
In the manufacture of semiconductor devices, the conductive paste used for die bonding requires properties such as bonding, conductivity, and heat dissipation, while also needing to prevent protrusion and contamination, especially as semiconductor packages have become smaller.
A conductive paste with specific viscosity characteristics is developed, measured using a BF type viscometer, which ensures excellent wetting and spreading between metal pieces and semiconductor elements, while suppressing protrusion and contamination. The paste has a viscosity of 100 Pa·s or more at 0.5 rpm and 21 Pa·s or less at 5 rpm, achieving a balanced set of properties.
The conductive paste provides improved thermal conductivity, connection reliability, and reduced contamination, resulting in a highly reliable semiconductor device with excellent product reliability.
Smart Images

Figure 0007661704000002 
Figure 0007661704000003 
Figure 0007661704000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paste, a highly thermally conductive material, and a semiconductor device. More specifically, the present invention relates to a conductive paste used as a semiconductor die attach paste used to bond and fix a semiconductor element to a support member such as a metal frame, a highly thermally conductive material obtained from the conductive paste, and a semiconductor device manufactured using the conductive paste. [Background technology]
[0002] Semiconductor devices in which a semiconductor element is mounted on a lead frame and molded with resin are widely used. For example, a semiconductor element such as an IC or LSI is mounted on a metal piece such as a lead frame and fixed using a conductive paste called a die attach paste, and then the lead part of the lead frame and the electrode on the semiconductor element are connected with a thin wire (bonding wire), and then these are housed in a package to form a semiconductor product. In addition, optical semiconductor devices using light-emitting diodes (LEDs) that are put into practical use for various displays are manufactured by bonding an optical semiconductor element to a predetermined part on a lead frame or a resin substrate with a conductive paste or the like, and then sealing it with a transparent sealing resin or the like (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-273407 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the manufacture of semiconductor devices, a resin paste for die bonding (conductive paste) is applied onto a metal piece such as a lead frame, a semiconductor element is then mounted, and the conductive paste is then cured and fixed. Since the cured product of the conductive paste is required to bond these components and to provide properties such as electrical conductivity and heat dissipation, the conductive paste needs to be able to sufficiently wet and spread between these components, and from this viewpoint, it is preferable for the viscosity to be low.
[0005] From the above viewpoint, it is sufficient that a layer made of conductive paste exists in the region directly below the semiconductor element. However, as shown in FIG. 5, when the semiconductor element 1 is mounted on the conductive paste 3 applied to the lead frame 2, the conductive paste protrudes laterally from the region A directly below the semiconductor element 1, forming a footing 3a (fillet 3a). The present inventors have found that when another component exists near the semiconductor element, the footing 3a may contaminate the other component. This problem has become apparent in recent years as the size of semiconductor packages has become smaller and other components have come to exist in positions close to the semiconductor element. In order to suppress the conductive paste from spilling out, it is preferable that the conductive paste has low wettability and spreadability, so there is a trade-off between the wettability and spreadability of the conductive paste and suppression of spillage. [Means for solving the problem]
[0006] The inventors have discovered that a conductive paste having a predetermined viscosity has excellent wetting and spreading properties between a metal piece such as a lead frame and a semiconductor element, and is also prevented from spilling out from the area directly below the semiconductor element, and have completed the present invention. That is, the present invention can be shown as follows.
[0007] According to the present invention, A conductive paste is provided, which has a viscosity (25°C) of 100 Pa·s or more when measured using a BF type viscometer at a rotation speed of 0.5 rpm, and a viscosity (25°C) of 21 Pa·s or less when measured at a rotation speed of 5 rpm.
[0008] According to the present invention, A highly thermally conductive material is provided by hardening the conductive paste.
[0009] According to the present invention, A substrate; A semiconductor element mounted on the base material via an adhesive layer, The adhesive layer is formed by curing the conductive paste according to any one of claims 1 to 12, thereby providing a semiconductor device. Effect of the Invention
[0010] According to the present invention, it is possible to provide a conductive paste that has excellent wetting and spreading properties between a metal piece such as a lead frame and a semiconductor element, excellent thermal conductivity and connectivity, and is also excellent in low contamination properties because it is suppressed from spilling out from the area directly below the semiconductor element. In other words, it is possible to provide a conductive paste that has an excellent balance of these properties. That is, a semiconductor device obtained using the conductive paste of the present invention has improved thermal conductivity, connection reliability, and contamination properties, and is excellent in product reliability. [Brief description of the drawings]
[0011] [Figure 1] 1 is a cross-sectional view illustrating an example of an electronic device according to an embodiment. [Diagram 2] 1 is a cross-sectional view illustrating an example of an electronic device according to an embodiment. [Diagram 3] 13 is a top view photograph of a semiconductor chip in a test piece created using the conductive paste of Example 2. [Figure 4] 13 is a photograph of a top view of a semiconductor chip in a test piece produced using the conductive paste of Comparative Example 3. [Diagram 5] 1 is a schematic partial cross-sectional view of a semiconductor device illustrating a problem to be solved by the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar reference symbols and their description will be omitted as appropriate. In addition, "~" indicates "above" to "below" unless otherwise specified.
[0013] The conductive paste of this embodiment satisfies both the following viscosity (1) and the following viscosity (2) measured using a BF viscometer (Brookfield viscometer). The conductive paste of this embodiment satisfies both the following viscosity (1) and the following viscosity (2), and thus has excellent wetting and spreading properties between a metal piece such as a lead frame and a semiconductor element, excellent thermal conductivity and connectivity, and also has excellent low contamination properties due to suppression of protrusion (footing and fillet formation) from the region directly below the semiconductor element, resulting in an excellent balance of these properties. In other words, a semiconductor device obtained using the conductive paste of the present invention has well-balanced improvements in thermal conductivity, connection reliability, and contamination properties, resulting in excellent product reliability.
[0014] (1) The viscosity (25°C) measured at a rotation speed of 0.5 rpm is 100 Pa s or more, preferably 105 Pa s or more, more preferably 110 Pa s or more, and particularly preferably 120 Pa s or more. The upper limit of the viscosity (1) is not particularly limited, but is about 2,000 Pa s or less from the viewpoint of wetting and spreading properties. (2) The viscosity (25°C) measured at a rotation speed of 5 rpm is 21 Pa s or less, preferably 20 Pa s or less, more preferably 19 Pa s or less, and particularly preferably 18 Pa s or less. There are no particular limitations on the upper limit of the viscosity (2), but from the viewpoint of suppressing protrusion from the region directly below the semiconductor element, it is about 1 Pa s or more. The numerical ranges of the viscosity (1) and the viscosity (2) can be appropriately combined.
[0015] Furthermore, the conductive paste of this embodiment can have a viscosity ratio ((1) / (2)) of the viscosity (1) at a rotation speed of 0.5 rpm and the viscosity (2) at a rotation speed of 5 rpm of 5.0 or more, preferably 5.2 or more, and more preferably 5.5 or more. If the viscosity of the conductive paste is within the above ratio range, it has excellent thixotropy, excellent wetting and spreading properties between metal pieces such as lead frames and semiconductor elements, and is further prevented from spilling out from the area directly below the semiconductor element, resulting in an even better balance of these properties.
[0016] The conductive paste of this embodiment further has a die shear strength measured under the following test conditions of 15 N or more, preferably 17 N or more, and more preferably 19 N or more. The upper limit is not particularly limited, but can be about 50 N or less.
[0017] (Test conditions) The conductive paste of this embodiment is applied onto an Au-plated copper frame to a coating thickness of 25±5 μm. Then, an Au-plated silicon chip measuring 2.0 mm in length × 2.0 mm in width × 350±5 μm in thickness is placed on the conductive paste. The temperature is raised from 30°C to 200°C over 60 minutes, and heat-treated at 200°C for 2 hours and then at 175°C for 4 hours to obtain a hardened body. The die shear strength of the Au-plated copper frame and the silicon chip at 260°C is measured for the hardened body.
[0018] The die shear strength in the above range is an indicator of a conductive paste having excellent bonding strength between a metal piece such as a lead frame and a semiconductor element. In other words, when preparing a conductive paste, by adjusting the composition so that the die shear strength satisfies the above range, a conductive paste having excellent bonding strength can be provided.
[0019] Furthermore, the conductive paste of this embodiment has a thermal conductivity of 9 W / mK or more, preferably 20 W / mK or more, and more preferably 30 W / mK or more, when cured.
[0020] When the thermal conductivity of the cured product is within the above range, the heat dissipation of the heat from semiconductor elements, etc. is excellent, and this is an indicator of a conductive paste having such excellent properties. In other words, when preparing a conductive paste, by adjusting the composition so that the thermal conductivity satisfies the above range, a conductive paste having excellent heat dissipation properties can be provided.
[0021] The conductive paste of this embodiment further has a fillet length measured under the following test conditions of 130 μm or less, preferably 105 μm or less, more preferably 90 μm or less, and particularly preferably 75 μm or less.
[0022] (Test conditions) The conductive paste is applied onto a copper frame to a thickness of 15±5 μm, and then a silicon chip measuring 1.3 mm in length × 1.2 mm in width × 350±5 μm in thickness is placed on the conductive paste with a load of 50 gf. When the conductive paste is allowed to wet and spread between the copper frame and the silicon chip, the distance that the conductive paste has spread from the area directly below the silicon chip (wet and spread distance, skirt length, fillet length) is measured.
[0023] The fillet length in the above range is an indicator of a conductive paste with excellent contamination suppression. In other words, when preparing a conductive paste, by adjusting the composition etc. so that the fillet length satisfies the above range, a conductive paste with excellent contamination suppression can be provided.
[0024] The conductive paste of this embodiment further has a wet-spreading area of the conductive paste directly under the silicon chip, measured under the test conditions for the fillet length, of 90% or more, preferably 95% or more, and more preferably 98% or more relative to 100% of the silicon chip area. The upper limit of the wet-spreading area is not particularly limited, but is preferably 100 or more from the viewpoint of product reliability.
[0025] When the wetting and spreading area is within the above range, it is possible to sufficiently bond between a metal piece such as a lead frame and a semiconductor element, and since the conductive paste has excellent electrical conductivity, thermal conductivity, and connectivity, it is an indicator of a conductive paste that has excellent product reliability and excellent production stability. In other words, when preparing a conductive paste, by adjusting the composition etc. so that the wetting and spreading area satisfies the above range, it is possible to provide a conductive paste that has excellent product reliability and excellent production stability.
[0026] The composition of the conductive paste of this embodiment that satisfies these characteristics will be described below. The conductive paste of this embodiment can satisfy the above characteristics by selecting the types and amounts of the components described below and adjusting the manufacturing conditions.
[0027] [Conductive filler] The conductive paste of the present embodiment may contain a conductive filler. When the conductive paste is subjected to a heat treatment, the conductive filler aggregates to form a metal particle connection structure. That is, in the die attach paste layer obtained by heating the conductive paste, the metal powder particles are present in an aggregated state. This allows electrical conductivity, thermal conductivity, and adhesion to the substrate to be exhibited.
[0028] The conductive filler used in the conductive paste of this embodiment may be silver powder, gold powder, platinum powder, palladium powder, copper powder, nickel powder, or alloys thereof. From the viewpoints of conductivity and ease of handling, it is preferable to use silver powder.
[0029] The shape of the conductive filler is not particularly limited, and examples thereof include spherical, flake, and scale shapes. In this embodiment, it is more preferable that the conductive filler contains spherical particles. This can improve the uniformity of the aggregation of the conductive filler. In addition, from the viewpoint of reducing costs, a mode in which the conductive filler contains flake particles can also be adopted. Furthermore, from the viewpoint of improving the balance between cost reduction and aggregation uniformity, the conductive filler may contain both spherical particles and flake particles.
[0030] Average particle size of conductive filler (D 50 ) is, for example, 0.1 μm or more and 10 μm or less. When the average particle size of the conductive filler is equal to or more than the above lower limit, the wetting and spreading properties are improved, and an excessive increase in the specific surface area is suppressed, making it possible to suppress a decrease in thermal conductivity due to contact thermal resistance. Furthermore, when the average particle size of the conductive filler is equal to or less than the above upper limit, protrusion from the region directly below the semiconductor element is suppressed, and it is possible to improve the formability of the metal particle connection structure between the conductive filler. Furthermore, from the viewpoint of improving the dispensability of the conductive paste, it is preferable that the average particle size (D 50 The average particle diameter (D) of the conductive filler is more preferably 0.6 μm or more and 2.7 μm or less, and particularly preferably 0.6 μm or more and 2.0 μm or less. 50 ) can be measured, for example, by using a commercially available laser type particle size distribution analyzer (for example, SALD-7000 manufactured by Shimadzu Corporation).
[0031] The maximum particle size of the conductive filler is not particularly limited, but may be, for example, 1 μm to 50 μm, more preferably 3 μm to 30 μm, and particularly preferably 4 μm to 18 μm, which makes it possible to more effectively improve the balance between the wetting and spreading properties and the suppression of the protrusion from the region directly below the semiconductor element.
[0032] The content of the conductive filler in the conductive paste affects the viscosity of the conductive paste, and from the viewpoint of the effects of the present invention, it is preferable that the content be, for example, 30% by mass or more and 80% by mass or less, and more preferably 40% by mass or more and 80% by mass or less, with respect to the entire conductive paste.
[0033] [Thermosetting resin] The conductive paste of the present embodiment may contain a thermosetting resin. The thermosetting resin may be one or more selected from cyanate resin, epoxy resin, resin having two or more radically polymerizable carbon-carbon double bonds in one molecule, and maleimide resin. Among these, it is particularly preferable to include an epoxy resin from the viewpoint of improving the effects of the present invention and the adhesiveness of the thermal conductive paste.
[0034] As the epoxy resin used as the thermosetting resin, any monomer, oligomer or polymer having two or more glycidyl groups in one molecule can be used, and there are no particular limitations on the molecular weight or molecular structure. Examples of the epoxy resin used in the present embodiment include biphenyl type epoxy resins; bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, and tetramethylbisphenol F type epoxy resin; stilbene type epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resin and cresol novolac type epoxy resin; multifunctional epoxy resins such as triphenolmethane type epoxy resin and alkyl-modified triphenolmethane type epoxy resin; aralkyl type epoxy resins such as phenol aralkyl type epoxy resin having a phenylene skeleton and phenol aralkyl type epoxy resin having a biphenylene skeleton; naphthol type epoxy resins such as dihydroxynaphthalene type epoxy resin and epoxy resin obtained by glycidyl etherifying a dimer of dihydroxynaphthalene; triazine nucleus-containing epoxy resins such as triglycidyl isocyanurate and monoallyl diglycidyl isocyanurate; and bridged cyclic hydrocarbon compound-modified phenol type epoxy resins such as dicyclopentadiene-modified phenol type epoxy resin. In addition, as the epoxy resin, for example, among compounds containing two or more glycidyl groups in one molecule, bisphenol compounds such as bisphenol A, bisphenol F, biphenol, or derivatives thereof, diols having an alicyclic structure such as hydrogenated bisphenol A, hydrogenated bisphenol F, hydrogenated biphenol, cyclohexanediol, cyclohexanedimethanol, cyclohexanediethanol, or derivatives thereof, aliphatic diols such as butanediol, hexanediol, octanediol, nonanediol, decanediol, or derivatives thereof, etc., epoxidized bifunctional ones, trifunctional ones having a trihydroxyphenylmethane skeleton, an aminophenol skeleton, etc. can be used. The epoxy resin as a thermosetting resin can contain one or more kinds selected from the above examples.
[0035] Among these, from the viewpoint of the effects of the present invention, it is more preferable to contain a bisphenol type epoxy resin, and it is particularly preferable to contain a bisphenol F type epoxy resin. Furthermore, in the present embodiment, from the viewpoint of more effectively improving the coating workability of the conductive paste, it is more preferable to contain a liquid epoxy resin that is liquid at room temperature (25° C.).
[0036] The cyanate resin used as the thermosetting resin is not particularly limited, but examples thereof include 1,3-dicyanatobenzene, 1,4-dicyanatobenzene, 1,3,5-tricyanatobenzene, 1,3-dicyanatonaphthalene, 1,4-dicyanatonaphthalene, 1,6-dicyanatonaphthalene, 1,8-dicyanatonaphthalene, 2,6-dicyanatonaphthalene, 2,7-dicyanatonaphthalene, 1,3,6-tricyanatonaphthalene, 4,4'-dicyanatobiphenyl, bis(4-cyanatophenyl)methane, bis(3,5-dimethyl-4-cyanatophenyl)methane, 2,2-bis(4-cyanatophenyl)methane, and the like. The polyfunctional cyanate resin may contain one or more selected from the group consisting of tris(4-cyanatophenyl)propane, 2,2-bis(3,5-dibromo-4-cyanatophenyl)propane, bis(4-cyanatophenyl)ether, bis(4-cyanatophenyl)thioether, bis(4-cyanatophenyl)sulfone, tris(4-cyanatophenyl)phosphite, tris(4-cyanatophenyl)phosphate, cyanates obtained by reacting a novolak resin with a cyanogen halide, and prepolymers having a triazine ring formed by trimerizing the cyanate groups of these polyfunctional cyanate resins. The prepolymers can be obtained by polymerizing the polyfunctional cyanate resin monomers using, for example, an acid such as a mineral acid or Lewis acid, a base such as a sodium alcoholate or a tertiary amine, or a salt such as sodium carbonate as a catalyst.
[0037] As the resin having two or more radically polymerizable carbon-carbon double bonds in one molecule used as the thermosetting resin, for example, a radically polymerizable acrylic resin having two or more (meth)acryloyl groups in the molecule can be used. In this embodiment, the acrylic resin can include a compound having a (meth)acrylic group, which is a polyether, polyester, polycarbonate, or poly(meth)acrylate having a molecular weight of 500 to 10,000. When a resin having two or more radically polymerizable carbon-carbon double bonds in one molecule is used as the thermosetting resin, the thermal conductive paste can include a polymerization initiator such as a thermal radical polymerization initiator.
[0038] The maleimide resin used as the thermosetting resin is not particularly limited, but may include one or more bismaleimide resins selected from, for example, N,N'-(4,4'-diphenylmethane)bismaleimide, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, etc.
[0039] The thermosetting resin may contain an epoxy resin having a biphenyl skeleton (biphenyl-type epoxy resin) as the resin having a biphenyl skeleton, which can improve the metal adhesion of the conductive paste.
[0040] The epoxy resin having a biphenyl skeleton is not particularly limited in structure as long as it has a biphenyl skeleton in its molecular structure and has two or more epoxy groups. For example, bifunctional epoxy resins obtained by treating biphenol or its derivatives with epichlorohydrin, phenol aralkyl type epoxy resins having a biphenylene skeleton, naphthol aralkyl type epoxy resins having a biphenylene skeleton, etc. may be used alone or in combination. Among these, those having two epoxy groups in the molecule are particularly preferred because they have excellent improvement in heat resistance. Examples of such epoxy resins include bifunctional epoxy resins obtained by treating biphenol derivatives with epichlorohydrin, such as biphenyl type epoxy resins and tetramethylbiphenyl type epoxy resins; phenol aralkyl type epoxy resins having a biphenylene skeleton, which have two epoxy groups (sometimes expressed as having two phenol nuclei); naphthol aralkyl type resins having a biphenylene skeleton, which have two epoxy groups; and the like.
[0041] From the viewpoint of the effects of the present invention, the content of the thermosetting resin in the conductive paste is, for example, 1 mass % or more and 15 mass % or less, preferably 2 mass % or more and 12 mass % or less, and more preferably 2.5 mass % or more and 10 mass % or less, based on the entire conductive paste.
[0042] (hardening agent) The conductive paste of the present embodiment may contain a curing agent. This can improve the curing property of the conductive paste. As the curing agent, for example, one or more selected from aliphatic amines, aromatic amines, dicyandiamide, dihydrazide compounds, acid anhydrides, and phenolic compounds can be used. Among these, it is particularly preferable to contain at least one of dicyandiamide and phenolic compounds from the viewpoint of improving production stability.
[0043] Examples of dihydrazide compounds used as curing agents include carboxylic acid dihydrazides such as adipic acid dihydrazide, dodecanoic acid dihydrazide, isophthalic acid dihydrazide, and p-oxybenzoic acid dihydrazide. Examples of acid anhydrides used as curing agents include phthalic acid anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, dodecenylsuccinic anhydride, a reaction product of maleic anhydride and polybutadiene, and a copolymer of maleic anhydride and styrene.
[0044] The phenol compound used as the curing agent is a compound having two or more phenolic hydroxyl groups in one molecule. The number of phenolic hydroxyl groups in one molecule is more preferably 2 to 5, and particularly preferably 2 or 3. This can more effectively improve the coating workability of the conductive paste, and can form a crosslinked structure during curing to provide excellent cured product properties of the conductive paste. The phenol compound may include one or more selected from bisphenols such as bisphenol F, bisphenol A, bisphenol S, tetramethyl bisphenol A, tetramethyl bisphenol F, tetramethyl bisphenol S, dihydroxydiphenyl ether, dihydroxybenzophenone, tetramethyl biphenol, ethylidene bisphenol, methyl ethylidene bis(methylphenol), cyclohexylidene bisphenol, and biphenol, trifunctional phenols such as tri(hydroxyphenyl)methane and tri(hydroxyphenyl)ethane, and derivatives thereof, and compounds obtained by reacting phenols such as phenol novolac and cresol novolac with formaldehyde, which are mainly binuclear or trinuclear, and derivatives thereof. Among these, it is more preferable to include bisphenols, and it is particularly preferable to include bisphenol F.
[0045] In this embodiment, a phenol resin (phenol compound) having a biphenyl skeleton can be used as the resin having a biphenyl skeleton as the curing agent. This can improve the conductivity of the conductive paste and the adhesion to the substrate. The phenol resin having a biphenyl skeleton is not particularly limited in structure as long as it has a biphenyl skeleton in its molecular structure and has two or more phenol groups.
[0046] From the viewpoint of the effects of the present invention, the content of the curing agent in the conductive paste is, for example, preferably 0.5 mass % or more and 10 mass % or less, and more preferably 1.0 mass % or more and 5 mass % or less, based on the entire conductive paste.
[0047] [(Meth)acrylate compounds] The conductive paste of the present embodiment may contain a (meth)acrylate compound. The (meth)acrylate compound is used as a reactive diluent having a reactive group involved in the crosslinking reaction of the binder resin contained in the conductive paste. As the (meth)acrylate compound, a monofunctional acrylic monomer having only one (meth)acrylic group, or a polyfunctional acrylic monomer having two or more (meth)acrylic groups can be used.
[0048] Examples of monofunctional acrylic monomers include 2-phenoxyethyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tridecyl (meth)acrylate, n-stearyl (meth)acrylate, isostearyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 2-ethylhexyl diethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and the like. p) acrylate, methoxydipropylene glycol (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, phenylphenol ethylene oxide modified (meth)acrylate, isobornyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate quaternized, glycidyl (meth)acrylate, neopentyl glycol (meth)acrylic acid benzoate, 1,Examples of the monofunctional acrylic monomer include 4-cyclohexanedimethanol mono(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalic acid, 2-(meth)acryloyloxyethyl acid phosphate, and 2-(meth)acryloyloxyethyl acid phosphate. The monofunctional acrylic monomer may be one or a combination of two or more of the above specific examples.
[0049] Of the above specific examples, it is preferable to use 2-phenoxyethyl methacrylate as the monofunctional acrylic monomer, from the viewpoints of the effects of the present invention and the adhesion of the resulting conductive paste to a base material.
[0050] Specific examples of polyfunctional acrylic monomers include ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, hexane-1,6-diol bis(2-methyl(meth)acrylate), 4,4'-isopropylidenediphenol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,6-bis((meth)acryloyloxy)-2,2,3,3,4,4,5,5-octadecane ... Examples of the methacrylic acid include fluorohexane, 1,4-bis((meth)acryloyloxy)butane, 1,6-bis((meth)acryloyloxy)hexane, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, N,N'-di(meth)acryloylethylenediamine, N,N'-(1,2-dihydroxyethylene)bis(meth)acrylamide, and 1,4-bis((meth)acryloyl)piperazine.
[0051] In this embodiment, from the viewpoint of the effects of the present invention and the adhesion of the resulting conductive paste to a substrate, the content of the (meth)acrylate compound in the conductive paste is preferably 0.5 mass % or more and 10 mass % or less, and more preferably 1.0 mass % or more and 5 mass % or less, based on the entire conductive paste.
[0052] [Organic solvents] The conductive paste of the present embodiment may contain an organic solvent, which is used as a non-reactive solvent that does not have a reactive group involved in the crosslinking reaction of the thermoplastic resin. By including an organic solvent, the fluidity of the resulting conductive paste can be adjusted, improving wettability and spreadability and suppressing overflow, and thus suppressing bleeding out of the additives.
[0053] Examples of organic solvents include alcohols such as ethyl alcohol, propyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, heptyl alcohol, octyl alcohol, nonyl alcohol, decyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl methoxybutanol, α-terpineol, β-terpineol, hexylene glycol, benzyl alcohol, 2-phenylethyl alcohol, isopalmityl alcohol, isostearyl alcohol, lauryl alcohol, ethylene glycol, propylene glycol, and glycerin; Ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), 2-octanone, isophorone (3,5,5-trimethyl-2-cyclohexen-1-one) or diisobutyl ketone (2,6-dimethyl-4-heptanone), gamma-butyrolactone; Esters such as ethyl acetate, butyl acetate, diethyl phthalate, dibutyl phthalate, acetoxyethane, methyl butyrate, methyl hexanoate, methyl octanoate, methyl decanoate, methyl cellosolve acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 1,2-diacetoxyethane, tributyl phosphate, tricresyl phosphate, or tripentyl phosphate; Ethers such as tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol monobutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, tripropylene glycol monobutyl ether, 1,2-bis(2-diethoxy)ethane, or 1,2-bis(2-methoxyethoxy)ethane; Ester ethers such as 2-(2-butoxyethoxy)ethane acetate; Ether alcohols such as 2-(2-methoxyethoxy)ethanol; Hydrocarbons such as toluene, xylene, n-paraffin, isoparaffin, dodecylbenzene, turpentine, kerosene or diesel; Nitriles such as acetonitrile or propionitrile; Amides such as acetamide or N,N-dimethylformamide; Examples of the oil include low molecular weight volatile silicone oil and volatile organic modified silicone oil.
[0054] In this embodiment, from the viewpoint of adjusting the viscosity of the conductive paste, the content of the organic solvent in the conductive paste is preferably 0.5 mass % or more and 15 mass % or less, and more preferably 1 mass % or more and 10 mass % or less, with respect to the entire conductive paste.
[0055] (Other Ingredients) In addition to the above-mentioned components, the conductive paste of the present embodiment may contain various additional components that are commonly used in the field, as necessary. The additional components include, but are not limited to, a silane coupling agent, a curing accelerator, a radical polymerization initiator, a stress reducing agent, an inorganic filler, etc., and can be selected according to the desired performance.
[0056] The curing accelerator is used to accelerate the reaction between the epoxy monomer used as a reactive diluent or the epoxy resin used as a binder resin and the curing agent. Examples of the curing accelerator include phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; amidines and tertiary amines such as dicyandiamide, 1,8-diazabicyclo[5.4.0]undecene-7, and benzyldimethylamine; and nitrogen atom-containing compounds such as quaternary ammonium salts of the above amidines or the above tertiary amines.
[0057] As the radical polymerization initiator, specifically, an azo compound, a peroxide, or the like can be used.
[0058] Examples of inorganic fillers include fused silica such as fused crushed silica and fused spherical silica, silica such as crystalline silica and amorphous silica, nanosilica, silicon dioxide, alumina, aluminum hydroxide, silicon nitride, and aluminum nitride. From the viewpoint of thixotropy control of the conductive paste, it is preferable to use nanosilica.
[0059] The nanosilica may be fumed silica or colloidal silica, and the particle size of the nanosilica is, for example, 1 nm to 100 nm, and preferably 2 nm to 50 nm.
[0060] (Preparation of conductive paste) The method for preparing the conductive paste is not particularly limited, but for example, the above-mentioned components are premixed, then kneaded using a triple roll, and further vacuum degassed to obtain a paste-like composition. In this case, the long-term workability of the conductive paste can be improved by appropriately adjusting the preparation conditions, for example, by performing the premixing under reduced pressure.
[0061] The viscosity of the conductive paste of this embodiment can be adjusted according to the application. The viscosity of the conductive paste can be controlled by adjusting the type of binder resin and the type of diluent used, the amount of each of them, etc. The lower limit of the viscosity of the conductive paste of this embodiment is For example, it is 10 Pa·s or more, preferably 20 Pa·s or more, and more preferably 30 Pa·s or more. This can improve the workability of the conductive paste. On the other hand, the upper limit of the viscosity of the conductive paste is, for example, 1×10 3 Pa s or less, preferably 5×10 2 Pa s or less, and more preferably 2×10 2 Pa·s or less, which can improve the coatability.
[0062] (Application) The applications of the conductive paste of this embodiment will be described. The conductive paste according to the present embodiment can be used as a highly thermally conductive material by hardening, and is used, for example, to bond a substrate and a semiconductor element to impart high thermal conductivity and high electrical conductivity. Examples of the semiconductor element include a semiconductor package and an LED. The conductive paste according to this embodiment has improved connection reliability and contamination resistance compared to conventional conductive pastes, and product reliability is improved. This makes it suitable for use when semiconductor elements that generate a large amount of heat are mounted on a substrate or when the size of a semiconductor package is small. In this embodiment, LED stands for light emitting diode.
[0063] Specific examples of semiconductor devices using LEDs include bullet-type LEDs, surface mount device (SMD) LEDs, COBs (Chip On Board), and power LEDs.
[0064] Specific types of the semiconductor packages include CMOS image sensors, hollow packages, Mold Array Packages (MAP), Quad Flat Packages (QFP), Small Outline Packages (SOP), Chip Size Packages (CSP), Quad Flat Non-leaded Packages (QFN), Small Outline Non-leaded Packages (SON), Ball Grid Arrays (BGA), Lead Flame BGAs (LF-BGA), Flip Chip BGAs (FC-BGA), Molded Array Process BGAs (MAP-BGA), Embedded Wafer-Level BGAs (eWLB), Fan-In type eWLB, and Fan-Out type eWLB.
[0065] An example of a semiconductor device using the conductive paste according to this embodiment will be described below. FIG. 1 is a cross-sectional view showing an example of a semiconductor device according to this embodiment. The semiconductor device 100 according to this embodiment includes a base material 30 and a semiconductor element 20 mounted on the base material 30 via an adhesive layer 10 which is a cured product of a conductive paste. The semiconductor element 20 and the base material 30 are electrically connected via, for example, a bonding wire 40. The semiconductor element 20 is sealed with, for example, a sealing resin 50.
[0066] Here, the lower limit of the thickness of the adhesive layer 10 is, for example, preferably 5 μm or more, and more preferably 10 μm or more. This improves the heat capacity of the cured product of the conductive paste, and improves the heat dissipation. The upper limit of the thickness of the adhesive layer 10 is, for example, preferably 50 μm or less, and more preferably 30 μm or less. This allows the conductive paste to exhibit suitable adhesion while improving the heat dissipation.
[0067] 1, the base material 30 is, for example, a lead frame. In this case, the semiconductor element 20 is mounted on the die pad 32 or the base material 30 via an adhesive layer 10. The semiconductor element 20 is also electrically connected to an outer lead 34 (base material 30) via, for example, a bonding wire 40. The base material 30, which is a lead frame, is made of, for example, a 42 alloy or a Cu frame.
[0068] The substrate 30 may be an organic substrate or a ceramic substrate. The organic substrate is preferably made of, for example, an epoxy resin, a cyanate resin, a maleimide resin, or the like. The surface of the substrate 30 may be coated with a metal such as silver or gold. This can improve the adhesion between the adhesive layer 10 and the substrate 30.
[0069] 2 is a cross-sectional view showing an example of the semiconductor device 100 according to the present embodiment, which is a modification of FIG. 1. In the semiconductor device 100 according to this modification, the base material 30 is, for example, an interposer. In the base material 30 which is an interposer, a surface on which the semiconductor element 20 is mounted and a surface opposite to the other surface are formed with, for example, a plurality of solder balls 52. In this case, the semiconductor device 100 is connected to another wiring board via the solder balls 52.
[0070] (Method of manufacturing a semiconductor device) An example of a method for manufacturing a semiconductor device according to this embodiment will be described. First, a conductive paste is applied onto the substrate 30, and then the semiconductor element 20 is placed thereon. That is, the substrate 30, the conductive paste, and the semiconductor element 20 are laminated in this order. There are no limitations on the method for applying the conductive paste, and specifically, dispensing, printing, inkjet, or the like can be used. The conductive paste of the present embodiment has excellent wetting and spreading properties between the substrate 30 and the semiconductor element 20, excellent thermal conductivity and connectivity, and suppresses protrusion (formation of a fillet) from the region directly below the semiconductor element 20, resulting in an excellent balance of these properties. In other words, the semiconductor device obtained by using the conductive paste of the present invention has improved thermal conductivity, connection reliability, and contamination resistance, resulting in excellent product reliability.
[0071] Next, the conductive paste is pre-cured and then post-cured to harden the conductive paste. By the heat treatment such as pre-curing and post-curing, the silver particles in the conductive paste are aggregated, and the interfaces between the multiple silver particles disappear, forming a thermally conductive layer in the adhesive layer 10. As a result, the substrate 30 and the semiconductor element 20 are bonded via the adhesive layer 10. Next, the semiconductor element 20 and the substrate 30 are electrically connected using a bonding wire 40. Next, the semiconductor element 20 is sealed with a sealing resin 50. In this way, a semiconductor device can be manufactured.
[0072] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted as long as they do not impair the effects of the present invention. EXAMPLES
[0073] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.
[0074] The components used in the examples and comparative examples are shown below. (thermosetting resin) -Epoxy resin 1: Diglycidyl ether of bisphenol F-epichlorohydrin (Nippon Kayaku Co., Ltd., RE-303SL, epoxy equivalent 160g / eq)
[0075] (hardening agent) - Hardener 1: Bisphenol F (DIC, DIC-BPF)
[0076] ((Meth)acrylate Compounds) -Acrylic monomer 1: 2-phenoxyethyl methacrylate (Kyoeisha Chemical Co., Ltd., Light Ester PO) -Acrylic monomer 2: polyethylene glycol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., NK Ester A-1000) -Acrylic monomer 3: 1,6-hexanediol dimethacrylate (Kyoeisha Chemical Co., Ltd., Light Ester 1,6HX)
[0077] (Radical initiator) - Radical initiator 1: Dicumyl peroxide (Perkadox BC, peroxide, manufactured by Kayaku Akzo Co., Ltd.) (Cure accelerator) -Cure accelerator 1: 2-phenyl-4,5-dihydroxymethylimidazole (manufactured by Shikoku Kasei, Curesol 2PHZ-PW)
[0078] (Conductive filler) -Silver filler 1: Spherical silver particles (DOWA Electronics, AG-DSB-114, D 50 :0.7μm) -Silver filler 2: flake-shaped silver particles (Fukuda Metal Foil and Powder Co., Ltd., HKD-16, median diameter 2.0 μm) -Silver filler 3: Flake-shaped silver particles (Tokuriki Honten Co., Ltd., TC-765, median diameter 2.1 μm)
[0079] (solvent) -Solvent 1: Tripropylene glycol mono n-butyl ether (Nippon Nyukazai Co., Ltd., BFTG) -Solvent 2: γ-butyrolactone (Wako Pure Chemical Industries, GBL)
[0080] (Conductive metal powder) -Silver powder 1: Flake-shaped silver powder (average particle size: 5.0 μm, manufactured by Tokuriki Chemical Co., Ltd., TKR-4A)
[0081] (Examples 1 to 5, Comparative Examples 1 to 4) <Preparation of Paste-like Adhesive Composition> First, a varnish-like mixture was prepared by kneading the components in the amounts listed in the "Varnish composition" in Table 1 at room temperature using a three-roll mill. Next, the obtained varnish-like mixture was mixed with silver powder and a solvent in the amounts listed in the "Paste composition" in Table 1, and the mixture was kneaded at room temperature using a three-roll mill to obtain a paste-like composition (conductive paste).
[0082] The conductive pastes of the respective Examples and Comparative Examples were evaluated for the following items. (viscosity) Using a BF viscometer (manufactured by Brookfield), the viscosity a at 25°C and a rotation speed of 0.5 rpm and the viscosity b at 25°C and a rotation speed of 5 rpm were measured. The viscosity ratio (a / b) was calculated from the obtained results. The results are shown in Table 1.
[0083] (Coverage) The obtained conductive paste was applied to a copper frame to a thickness of 15±5μm, and then a silicon chip with a length of 1.3mm, width of 1.2mm, and thickness of 350±5μm was placed on the conductive paste with a load of 50gf, and the conductive paste was spread between the copper frame and the silicon chip. The wetted and spread area was calculated relative to the area of the silicon chip (100%) by binarization. FIG. 3 shows a photograph of the top surface of a semiconductor chip in a test piece created using the conductive paste of Example 2, and FIG. 4 shows a photograph of the top surface of a semiconductor chip in a test piece created using the conductive paste of Comparative Example 3.
[0084] (Fillet length) As in the above wet spreadability test, the conductive paste was spread between the copper frame and the silicon chip. The distance that the conductive paste spread from the end of the silicon chip (foot length, fillet length) was measured using a laser microscope (Keyence Corporation, VK-X1000).
[0085] (Die shear strength) The conductive paste obtained was applied to an Au-plated copper frame to a thickness of 25±5 μm, and then an Au-plated silicon chip measuring 2.0 mm long x 2.0 mm wide x 350±5 μm thick was placed on the conductive paste. The temperature was then raised from 30° C. to 200° C. over 60 minutes, and the chip was heat-treated at 200° C. for 2 hours and then at 175° C. for 4 hours to obtain a hardened product. The die shear strength of the Au-plated copper frame and the silicon chip at 260° C. was measured for this hardened product.
[0086] (Thermal Conductivity) The obtained paste-like resin composition was applied onto a Teflon plate, and the temperature was raised from 30° C. to 200° C. over 60 minutes in a nitrogen atmosphere, followed by heat treatment at 200° C. for 120 minutes. This resulted in a heat-treated paste-like resin composition having a thickness of 1 mm (Teflon is a registered trademark of fluororesin). Next, the thermal diffusion coefficient α of the heat-treated body in the thickness direction was measured by a laser flash method at a temperature of 25°C. In addition, the specific heat Cp was measured by differential scanning calorimetry (DSC). Furthermore, the density ρ was measured in accordance with JIS K 6911. Using these values, the thermal conductivity λ was calculated based on the following formula. Thermal conductivity λ[W / (m·K)]=α[m 2 / sec]×Cp[J / kg K]×ρ[g / cm 3 ]
[0087] [Table 1] [Explanation of symbols]
[0088] 100 Semiconductor device 10 Adhesive layer 20 Semiconductor elements 30 Base material 32 Die pad 34 Outer lead 40 Bonding Wire 50 Sealing resin 52 Solder ball 1. Semiconductor element 2 Lead Frame 3. Conductive paste 3a Fillet
Claims
1. A conductive paste used to bond a semiconductor element and a metal by hardening, comprising: (A) a conductive filler; (B) a thermosetting resin; and (C) a (meth)acrylate compound; and (D) a curing agent; and Including, (D) the curing agent contains a phenol compound, The viscosity (25°C) measured using a BF type viscometer at a rotation speed of 0.5 rpm is 100 Pa s or more, A conductive paste having a viscosity (25°C) measured at a rotation speed of 5 rpm of 21 Pa·s or less.
2. 2. The conductive paste according to claim 1, having a die shear strength of 15 N or more measured under the following test conditions. (Test conditions) The conductive paste is applied onto an Au-plated copper frame to a coating thickness of 25±5 μm, and then an Au-plated silicon chip measuring 2.0 mm in length × 2.0 mm in width × 350±5 μm in thickness is placed on the conductive paste. The temperature is raised from 30° C. to 200° C. over 60 minutes, and the chip is heat-treated at 200° C. for 2 hours and then at 175° C. for 4 hours to obtain a hardened body. The die shear strength of the hardened body between the Au-plated copper frame and the silicon chip at 260° C. is measured.
3. 3. The conductive paste according to claim 1, wherein the cured product has a thermal conductivity of 9 W / mK or more.
4. The conductive paste according to any one of claims 1 to 3, wherein the fillet length measured under the following test conditions is 130 µm or less. (Test conditions) The conductive paste is applied onto a copper frame to a thickness of 15±5 μm, and then a silicon chip measuring 1.3 mm in length × 1.2 mm in width × 350±5 μm in thickness is placed on the conductive paste with a load of 50 gf. When the conductive paste is allowed to wet and spread between the copper frame and the silicon chip, the distance that the conductive paste has spread from the area directly below the silicon chip (fillet length) is measured.
5. 5. The conductive paste according to claim 4, wherein a wetting and spreading area of the conductive paste relative to 100% of the silicon chip area measured under the test conditions is 90% or more.
6. A conductive paste described in any one of claims 1 to 5, further comprising (E) an organic solvent.
7. (A) A conductive paste described in any one of claims 1 to 6, wherein the conductive filler contains silver powder.
8. (A) A conductive paste as described in Claim 7, wherein the silver powder contained in the conductive filler includes flake-shaped silver particles and spherical silver particles.
9. A conductive paste described in any one of claims 1 to 8, wherein (B) the thermosetting resin includes an epoxy resin.
10. A conductive paste described in any one of claims 1 to 9, wherein the (C) (meth)acrylate compound includes a monofunctional acrylic monomer having only one (meth)acrylic group, or a polyfunctional acrylic monomer having two or more (meth)acrylic groups.
11. (E) A conductive paste as described in claim 6, wherein the organic solvent includes an ether.
12. A conductive paste described in any one of claims 1 to 11, wherein (A) the conductive filler is contained in an amount of 30 mass% or more and 80 mass% or less relative to the entire conductive paste.
13. A conductive paste described in any one of claims 1 to 12, wherein (B) the thermosetting resin is contained in an amount of 1 mass % or more and 15 mass % or less with respect to the entire conductive paste.
14. A conductive paste described in any one of claims 1 to 13, wherein (C) a (meth)acrylate compound is contained in an amount of 0.5 mass% or more and 10 mass% or less with respect to the entire conductive paste.
15. A conductive paste described in any one of claims 1 to 14, wherein (D) a hardener is contained in an amount of 0.5 mass % or more and 10 mass % or less relative to the entire conductive paste.
16. A conductive paste as described in claim 6, wherein (E) the organic solvent is contained in an amount of 0.5 mass% or more and 15 mass% or less relative to the entire conductive paste.
17. A highly thermally conductive material obtained by hardening the conductive paste according to any one of claims 1 to 16.
18. A substrate made of a metal or a substrate having a surface coated with a metal, a semiconductor element mounted on the metal via an adhesive layer; The adhesive layer is formed by hardening the conductive paste according to any one of claims 1 to 16.
Citation Information
Patent Citations
Semiconductor light emitting device
JP2003273407A
Die bonding paste and semiconductor device using the same
JP2008174577A
Method of manufacturing semiconductor chip laminate, and semiconductor device
JP2011009765A
Adhesive composition
JP2018513891A
Thermally conductive paste and electronic device
US20190338171A1